Inkonsistensi Aturan Keterwakilan Perempuan dalam Pelakasanaan Pemilu 2024 dalam Perspektif Feminis Legal Teori - Haviz, Fauzan; Viona, Asi Nanda; Ramadhan, Adit Nazmi; Srimufi, Mela; Albert, Eko; Mairul, Mairul (ASOSIASI IDEBAHASA KEPRI, 2025)
Abstract The women's movement in Indonesia has active involvement in the political field, but there is still a gap in terms of women's participation and representation in formal political structures. Women's political representation is quite important if we want to have a gender-friendly democracy. After the publication of PKPU number 10 of 2023, the position of women was degraded and of course this is very dangerous for gender equality, the existence of this provision gave rise to a polemic in terms of the hierarchy of PKPU statutory regulations, which directly contradicts Law number 7 of 2017 concerning elections which states women's representation is at least 30%, legal feminist theory sees that this representation figure actually makes women's position weaker. The type of research used is library research using the statutory approach method. Meanwhile, the analysis used is juridical-normative analysis, where in this case the author will describe an event by providing analysis through the lens that the author uses. through theories, principles, concepts and other things that are interrelated. Whereas the regulations issued by the KPU, namely PKPU number 10 of 2023, place women's position in a reductive marginal position in politics or the arena of political contestation in 2024. Whereas from the perspective of feminist legal theory its nature is rejection or refusal, this theory emphasizes the aspect of equality based on arguments. and also ideology, a feminist legal theory perspective certainly rejects the 30% female representation figure because it directly makes women marginal-reduce. Keywords— elections, women's representation, feminist legal theory